Konstruksi Hukum Riba dan Bunga Bank: Implikasi Terhadap Regulasi Perbankan Syariah di Indonesia - Zidni Ilman Nafi'an; Muhammad Yunus (Mutawasith: Jurnal Hukum Islam, 2025)
This research aims to analyse the fundamental differences between the concept of usury in Islamic law and bank interest in the modern financial system, as well as how it affects the formation of Islamic banking regulations in Indonesia. Using a normative juridical research method with a conceptual and statutory approach, this study analyses various primary and secondary legal sources, including the Quran, Hadith, DSN-MUI fatwas, and Islamic banking legislation. The results show that the legal construction of usury in Islam has a broader dimension than the concept of bank interest. Islamic banking regulations in Indonesia have attempted to accommodate sharia principles, but still face challenges in harmonising with the existing conventional banking system. The dualism of the banking system in Indonesia requires a more comprehensive regulatory framework to regulate the interaction between Islamic and conventional banking. Policy reformulation is needed that accommodates the unique characteristics of Islamic banking and maintains the stability of the national financial system. This study provides theoretical contributions in the development of Islamic banking law and practical recommendations for regulatory reform of the banking sector in Indonesia.